Pengenalan Bahaya “BACKDRAFT” Bagi Siswa-Siswi Sekolah Menengah Atas dan Sekolah Menengah Kejuruan di Indonesia - Oke Hendra; Ika Endrawijaya; Wahyu Kurniawan; Martha Saulina; Wildan Nugraha (Darmabakti: Jurnal Inovasi Pengabdian dalam Penerbangan, 2022)
Fires are very common disasters found both on a small scale and on a large scale. However, there are still many people who still do not understand and have not been well educated about fire safety, so many of the ordinary people cannot do much if there is a fire in the area around them, as well as in public facilities. The purpose of this community service activity is to introduce the dangers of backdraft in fire events to ordinary people, especially high school and vocational high school students who are the next generation of young people in the nation so as not to cause casualties. The method used in these activities is a presentation delivered by the resource persons in this case are lecturers and cadets of the Aircraft Accident Relief study program and then continued with questions and answers with participants from senior high school and vocational high school from several region in Indonesia who have registered. This activity is carried out online through a video conferencing application. The result obtained from the activities is that participants gain knowledge related to the dangers of the "backdraft" by knowing what, how it happened, and how to avoid it, and what needs to be done so that there is no "backdraft" in the event of a fire. The introduction of "backdraft" activities in fire events is expected to minimize casualties from the general public when there is a "backdraft" in a fire event.